Association of antihypertensive therapy intensification on blood pressure control and atherosclerotic cardiovascular disease (ASCVD) risk: a retrospective cohort study in Bali, Indonesia - I Putu Denta Nugraha Parahyangan; Dita Maria Virginia; Phebe Hendra (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2025)
Background: Hypertension is a major ASCVD risk factor, especially among elderly and diabetic patients. Appropriately intensifying antihypertensive therapy may improve blood pressure (BP) control and reduce ASCVD risk. Objective: This study evaluated the effect of antihypertensive therapy intensification on BP outcomes and 10-year ASCVD risk among hypertensive patients in Bali, Indonesia. Methods: A retrospective cohort study included hypertensive patients aged 40–74 years receiving outpatient care at regional public hospitals in Bali (January–December 2024). Therapy intensification was assessed using a guideline-based treatment intensification (TI) score; primary outcomes were final BP and estimated 10-year ASCVD risk. Results: Of 191 patients (median age 62 years; 75.9% with type 2 diabetes mellitus), those with appropriate therapy intensification achieved significantly lower systolic BP than those with inappropriate intensification (122.77 vs. 143.28 mmHg; p < 0.001) and were more likely to attain controlled BP (OR = 63.462; 95%CI: 8.017–502.354; p < 0.001; estimate based on a small reference cell). Each 0.1-unit increase in the TI score was associated with a 0.35% reduction in estimated ASCVD risk (p < 0.001). Conclusion: Appropriate antihypertensive therapy intensification was associated with significantly better blood pressure control, with a non-significant tendency toward below-target BP among patients receiving appropriate intensification.